2022
DOI: 10.1039/d1tc03614a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis, precise species control and chemical transformation of highly conducting organic metal chalcogenides CuxBHT (BHT = benzenehexathiol; x = 3, 4, and 5.5)

Abstract: The design of conducting organic metal chalcogenides (OMCs) have attracted extensive attention for their applications in diverse areas. However, only a handful of OMCs exhibit appealing electrical transport properties due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Cu x BHTs were synthesized by changing stoichiometric ratios of Cu 2 O to BHT according to our group's previous report. [ 16 ] As shown in Figure a–c, the XRD patterns of Cu 3 BHT, Cu 4 BHT and Cu 5.5 BHT prepared by Cu 2 O and BHT are exactly the same as previously reported, [ 13,15 ] indicating that they have the same crystal structure. Furthermore, the element analysis and XPS results prove that the obtained samples have the same chemical composition as the previously reported samples (see Synthesis of Cu x BHT and Figure S1a–c, Supporting Information).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Cu x BHTs were synthesized by changing stoichiometric ratios of Cu 2 O to BHT according to our group's previous report. [ 16 ] As shown in Figure a–c, the XRD patterns of Cu 3 BHT, Cu 4 BHT and Cu 5.5 BHT prepared by Cu 2 O and BHT are exactly the same as previously reported, [ 13,15 ] indicating that they have the same crystal structure. Furthermore, the element analysis and XPS results prove that the obtained samples have the same chemical composition as the previously reported samples (see Synthesis of Cu x BHT and Figure S1a–c, Supporting Information).…”
Section: Resultssupporting
confidence: 84%
“…In addition, it has been found that Cu 4 BHT and Cu 5.5 BHT can be converted into Cu 3 BHT by chemical oxidation. [ 16 ] This prompted us to explore whether the electrochemical method can complete this transformation. The results show that Cu 4 BHT and Cu 5.5 BHT can be easily converted to Cu 3 BHT by simply performing a CV cycle within −1.2 to 0.5 V. As illustrated in Figure S19a,b (Supporting Information), the XRD patterns of Cu 4 BHT and Cu 5.5 BHT both show the peak corresponding to Cu 3 BHT located at 2θ = 26.1°, revealing the occurrence of the structural transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the structural transformation achieved by chemical oxidation was a synthetic shortcut to prepare OMCs 21 . To testify the universality of this chemical transformation strategy for OMCs, valence-variable cerium ammonium nitrate ((NH 4 ) 2 Ce(NO 3 ) 6 , CAN) was employed as the oxidizing reagent here (Methods, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reported conductive CPs with this type of ligand have two typical 2D structure patterns, one is a honeycomb structure with a ligand-to-metal ratio of 3:1 , and the other is a Kagomé lattice with a molar ratio of 3:2. , Despite their excellent performance, unfortunately, the lack of structural diversity and the finite choice of such ligands limit their wider research to a certain extent. However, our recent study on Cu–BHT CPs , shows that using the same metal nodes and organic ligands a series of (Cu x BHT) n ( x = 3, 4, 5.5) with different structures can be synthesized by regulating the oxidation levels of the ligands. Newly synthesized (Cu 4 BHT) n and (Cu 5.5 BHT) n have 3D structures, which are different from other conductive CPs based on BHT-like ligands.…”
Section: Introductionmentioning
confidence: 99%